The Impact of Temporary Protected Status on Immigrants' Labor Market Outcomes - Pia M. Orrenius; Madeline Zavodny (Institute for the Study of Labor (IZA), 2014)
The United States currently provides Temporary Protected Status (TPS) to more than 300,000 immigrants from selected countries. TPS is typically granted if dangerous conditions prevail in the home country due to armed conflict or a natural disaster. Individuals with TPS cannot be deported and are allowed to stay and work in the United States temporarily. Despite the increased use of TPS in recent years, little is known about how TPS affects labor market outcomes for beneficiaries, most of whom are unauthorized prior to receiving TPS. This study examines how migrants from El Salvador who are likely to have received TPS fare in the labor market compared with other migrants. The results suggest that TPS eligibility leads to higher employment rates among women and higher earnings among men. The results have implications for recent programs that allow some unauthorized immigrants to receive temporary permission to remain and work in the United States.
Keywords: J15; J31; J61; 330; immigration policy; unauthorized immigration; temporary protected status; TPS